Transnational death - Saramo, Samira; Koskinen-Koivisto, Eerika; Snellman, Hanna, 1961-; Alonso Ortiz, Ana D.; Suomalaisen Kirjallisuuden Seura (Helsinki : Finnish Literature Society (SKS), 2019)
Abstract.
Transnational death brings together eleven cutting-edge articles from the emerging field of transnational death studies. The collection highlights European, Asian, North American, and Middle Eastern perspectives, and reflects on people's changing experiences with death in the context of migration over time. The collection begins with a thematic assessment of transnational death studies, and then examines case studies, divided into Family, Community, and Commemoration sections. Together, the chapters provide new insights on issues including identity and belonging, community reciprocity, transnational communication, and spaces of mourning and commemoration.
Introductory essay : Making transnational death familiar / Samira Saramo -- Negotiating belonging through death among Finnish immigrants in Sweden / Hanna Snellman -- Doing death kin work in Polish transnational families / Anna Matyska -- The emotional costs of being unable to attend the funeral of a relative in one's country of origin / Josiane Le Gall and Lilyane Rachédi -- Expressing communality : Zapotec death and mourning across transnational frontiers / Lourdes Gutiérrez Nájera and Ana D. Alonso Ortiz -- The spirit of the gift : Burmese Buddhist death rituals in North America / Chipamong Chowdhury -- Genealogies of death : repatriation among Moroccan and Senegalese in Catalonia / Jordi Moreras and Ariadna Solé Arraràs -- Our foreign hero : a Croatian goalkeeper and his Swedish death / Katarzyna Herd -- Coping with the consequences of terror : the transnational visual narratives of Coptic Orthodox martyrdom / Cordula Weisskoeppel -- Transnationally forgotten and re-remembered : Second World War Soviet mass graves at Mäntyvaara, eastern Finnish Lapland / Oula Seitsonen -- Transnational heritage work and commemorative rituals across the Finnish-Russian border in the old Salla region / Eerika Koskinen-Koivisto.
Artikkelien kirjoittajat: Ana D. Alonso Ortiz ja 13 muuta.
Keywords: transnationaalisuus; siirtolaisuus; suvut; perheet; yhteenkuuluvuus; yhteisöllisyys; kuolema; perheenjäsenet; sukulaiset; ulkomaat; uhrit; sodat; muistomerkit; muistotilaisuudet